Terapi Bekam: Efek Anti Peradangan dalam Pengobatan Tradisional - Wahyuni, Dian; Legiran, Legiran; Saleh, Irsan; Salim, Eddy Mart (Fakultas Kedokteran Universitas Trisakti, 2024)
This comprehensive literature review consolidates findings from 11 diverse scholarly articles exploring the efficacy of cupping therapy as an anti-inflammatory intervention. The review encompasses studies investigating various clinical applications and experimental models to delineate the therapy's anti-inflammatory effects. The research method utilized the Publish or Perish application to access databases such as PubMed, Scopus, and Google Scholar. The screening process was based on predetermined inclusion and exclusion criteria. Article quality was assessed using the Crowe Critical Appraisal Tool (CCAT). Standard forms were used to extract important information from articles: Authors’ name, Year; Research title; Population; data; Findings. Data were analyzed narratively to generate thematic synthesis. The reviewed studies revealed significant outcomes across multiple domains. Clinical trials demonstrated the efficacy of cupping therapy in managing pain in osteoarthritis and idiopathic menorrhagia. Narrative reviews and experimental studies highlighted its potential in sports injury management and its influence on changes in local blood flow. Additionally, investigations provided insights into its immunomodulatory effects in cancer patients, allergic asthma models, and inflammatory conditions like acute herpes zoster. Synthesizing these findings emphasized the diverse anti-inflammatory effects of cupping therapy across various health conditions, elucidating its mechanisms and potential applications. The therapy exhibited promising outcomes in pain management, inflammation reduction, and modulation of immune responses.